ANALISA LAPORAN KEUANGAN UNTUK MENETAPKAN KINERJA KEUANGAN PERUSAHAAN - Yaneke Pingkan Boyoh; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The method in this research is to use the literature study method. The data collection techniques are by reading, recording, verifying data related to research. The data used come from textbooks, journals, scientific articles, literature reviews related to the topic under study. The data processing technique is by verifying the material obtained and reviewing it in accordance with answering the identification of the problem.